A model for evaluating menu performance in collective nutrition organizations based on the DEA method - Arsić, Slaviša N.; Pamučar, Dragan S.; Milenkov, Marjan A.; Sokolović, Vlada S.; Janošević, Miljojko M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: In the paper, a model for evaluating menu performance in collective nutrition organizations is presented, enabling quantification of the efficiency of each individual dish.Methods: The Data Envelopment Analysis (DEA) method has been applied to evaluate the efficiency of dishes.Results: The model has been successfully tested on the menu of the collective nutrition restaurant for cadets at the Military Academy in Belgrade (MAB). The evaluation included 20 existing dishes and 11 substitute dishes formed using the Food Replacement Table (FRT), allowing insight into the efficiency of each individual dish. In line with the specified criteria, 10 out of a total of 31 dishes have been evaluated as efficient (7 existing and 3 replacement dishes). By replacing inefficient existing dishes with new efficient dishes, the overall efficiency of the menu will increase, implying greater satisfaction of food users and reduction of the waste of prepared and uneaten meals.Conclusion: A proposed model can be applied in practice because it provides objective and measurable values for assessing the performance of dishes, aiming to optimize the menu assortment in collective nutrition organizations and reduce the shortcomings of subjective decision making in selecting substitute meals. This model can be further improved by the use of other different methods for determining the weights of the criteria and ranking.
Keywords: menu evaluation; restaurant management; DEA method; collective nutrition